Prevalent and Severe Conditions That Compromise the Welfare of Shelter Dogs: Opinions from the Taiwanese Experts - Chen, Yu-Hsin; Chen, Ching-I; Lin, Chen-Yan; Teng, Kendy Tzu-yun (Animals (Basel), 2025)
The welfare of shelter dogs is a growing concern, particularly in regions like Taiwan, where public animal shelters (PASs) often face overcrowding. This study aimed to identify and prioritise welfare conditions (WCs) affecting shelter dogs in Taiwan’s PASs, offering insights into their impacts on population and individual welfare. A modified Delphi approach engaged 14 experts to evaluate the prevalence, severity, and duration of 59 potential WCs using the Five Domains model. The welfare impact of each WC on individual dogs was assessed as the product of severity and duration, with WCs scoring a median of 3 or higher considered critical. Of the 59 identified WCs, 49 were deemed critical. The most prevalent WCs were “limited access to toys” (median = 4.00), “insufficient foraging opportunities” (median = 4.00), and “intermittent, excessive barking noise” (median = 4.00). The most impactful WCs for individual dogs were “depressive disorders” (median of the product of duration and severity scores = 16.00), “fear-related or anxiety disorders” (median = 15.00), and “limited space” (median = 15.00). The Physical Environment Domain and the Behavioural Interactions Domain were highlighted as having the most significant and prolonged negative effects on welfare. This study provides a comprehensive WC list for shelter dogs, guiding future welfare improvements and resource allocation strategies.